Aktivitas Kolinesterase pada Petani: Studi Deskriptif Pajanan Pestisida - Putri Wulandari; Dian Wuri Astuti; Siti Fatimah (Media Literasi Indonesia, 2026)
Excessive use of pesticides by farmers, especially without adequate Personal Protective Equipment (PPE), carries the risk of health problems such as decreased cholinesterase enzyme activity. Exposure to pesticides particularly organophosphates, can cause poisoning through the mouth, skin, and respiratory tract. Organophosphates work by inhibiting the acetylcholinesterase enzyme, causing an accumulation of acetylcholine in the body. Pesticide residues also have the potential to cause neurological and hormonal disorders, and even carcinogenesis. Yogyakarta is one of the regions with the highest number of pesticide poisoning cases. Increasing farmers' knowledge about the dangers of pesticides and the use of PPE are needed to reduce health risks. The aim of research was to determine the activity of the cholinesterase enzyme in the Wono Rejo Selopamioro Farmer Group, Imogiri, Bantul, Special Region of Yogyakarta. This study is a descriptive study. The sample in this study was the serum of 13 respondents. The examination in this study used the Kinetic Photometric Test method. A study of cholinesterase enzyme activity in the blood showed that four respondents (31%) experienced pesticide poisoning, with concentrations of 3,973 U/L, 4,316 U/L, 3,973 U/L, and 4,418 U/L.